Biomechanical engineering of textiles and clothing - Li, Y. (Yi), 1958-; Dai, X.-Q. (Xiaoqun) (Woodhead publishing in textiles., 2006)
Biomechanical engineering of textiles and clothing addresses the issues of designing and producing textiles and clothing for optimum interaction with the body. It covers fundamental theories, principles and models behind design and engineering for the body's biomechanics. Contact problems arising between textiles/clothing and the body are discussed along with the mechanics of fibres, yarns, textiles and clothing. Material properties are also covered in relation to mechanical performance.